2017
DOI: 10.24001/ijaems.3.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Free cashflow and firm performance: Evidence from sectoral levels for Vietnamese listed firms

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…Hence, free cash flow is significantly giving a positive impact on firm performance. Our results are supported by a previous study by Hau (2017) which indicates that when a firm has investments opportunities, the free cash flow may significantly increase firm performance. This finding is also in line with the study by Wang (2010) and Gregory (2005) where free cash flows could render a firm with investment journal.ump.edu.my/jgi ◄ opportunities that would generate more value for the firm.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Hence, free cash flow is significantly giving a positive impact on firm performance. Our results are supported by a previous study by Hau (2017) which indicates that when a firm has investments opportunities, the free cash flow may significantly increase firm performance. This finding is also in line with the study by Wang (2010) and Gregory (2005) where free cash flows could render a firm with investment journal.ump.edu.my/jgi ◄ opportunities that would generate more value for the firm.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, free cash flow has a significant positive impact on asset return. Our findings are supported by Hau (2017), who claims that when a firm has investment opportunities, free cash flow can significantly improve firm performance. This is also consistent with the study from Wang (2010) whereby there is a lack of evidence supporting the free cash flows hypothesis, where free cash flows could reduce for firms with investment opportunities which would generate more values for the firm.…”
Section: Findings and Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The result showed a positive relationship between free cash flow and profitability. [18], conducted a study on the impact of free cash flows on the output of the Vietnam-listed manufacturing and real estate companies. The study revealed a positive relationship between cash flows across all industries and company profitability.…”
Section: Empirical Reviewmentioning
confidence: 99%